Gibberellic acid reduces clusters rot of ‘sauvignon blanc’ grapes ácido giberélico reduz a podridão dos cachos de uvas ‘sauvignon blanc’ - Da Silva P.S.* (2019)
© 2019, Sociedade Brasileira de Fruticultura. All rights reserved.The ripening of grapes is impaired by climatic conditions due to the prolonged rainy season and thus facilitates the proliferation of diseases such as grape clusters rotting, caused by the fungus Botrytis cinerea, even before the ideal harvesting point. The aim of the study was to evaluate the effect of gibberellic acid (GA3) on rot and on physical-chemical quality of ‘Sauvignon Blanc’ grapevine. The experiment was carried out in the production season of 2016 and 2017 in Campanha region in Rio Grande do Sul, Brazil. The GA3 treatments were at the doses of 0 (control); 2; 4; 6 and 8 mg L-1 of GA3. The percentage of clusters rotting and maturation index decreased, however, the titratable acidity increased with GA3 doses. The cluster and rachis length increased with application of GA3. The cluster width; cluster, rachis and berry mass and the soluble solids were not influenced by application of GA3. In ‘Sauvignon Blanc’ grapevine, GA3 reduced the percentage of clusters rotting and improved the cluster and rachis length characteristics and titrable acidity.